2017
DOI: 10.1590/0034-737x201764050003
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological variables and morphological characteristics influencing the evapotranspiration of forage cactus

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…ET C and k C fluctuated according to the growth dynamics of the crop and the influence of more intense rainfall events. Barbosa et al (2017a) state that evapotranspiration in the forage cactus depends on the seasonality of the weather conditions and the morphological characteristics of the species. Under full growth and maximum productivity, the ET C and k C reflect the water requirement of the crop to be adopted under irrigation management (Pereira et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ET C and k C fluctuated according to the growth dynamics of the crop and the influence of more intense rainfall events. Barbosa et al (2017a) state that evapotranspiration in the forage cactus depends on the seasonality of the weather conditions and the morphological characteristics of the species. Under full growth and maximum productivity, the ET C and k C reflect the water requirement of the crop to be adopted under irrigation management (Pereira et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mulching, for example, affords protection, maintenance of the soil moisture and lower thermal amplitude, in addition to providing nutrients and improving physical and biological attributes (Namaghi et al, 2018), while irrigation offers stability of the soil moisture and guarantees adequate crop growth. Some studies have been carried out in the Brazilian semi‐arid region on irrigation in the forage cactus (Queiroz et al, 2016; Barbosa et al, 2017a,b), but there are gaps regarding the use of mulch (Carvalho et al, 2017). Furthermore, few studies have reported on the water requirement of the cactus (Queiroz et al, 2016; Lima et al, 2018), which has to be measured under optimal growth conditions (Morais et al, 2017; Lima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The SWB is one of the most common methods for quantifying water consumption in various crops, including forage cactus cropping systems (Barbosa et al, 2017a(Barbosa et al, , 2017bLima et al, 2018;Pereira et al, 2017;Queiroz et al, 2015Queiroz et al, , 2016Silva et al, 2014Silva et al, , 2015. However, due to the high volume of moisture retained in the forage cactus cladodes (approximately 90%), the use of the SWB without considering the amount of water retained by the plant can overestimate the actual ET of the crop by up to 5.4%.…”
Section: Swb and Etmentioning
confidence: 99%
“…Entre as diversas forrageiras que existem no semiárido brasileiro, como gramíneas e plantas nativas, esta cactácea destaca-se em virtude dos seus mecanismos de adaptações à escassez de água, o que permite a sua perenidade em ambientes de extrema condição de aridez, mantendo a sustentabilidade da pecuária no semiárido, proporcionando produção quantitativa e qualitativa, através da melhoria na dieta alimentar a custos razoáveis para os produtores rurais (Alencar et al, 2011;Barbosa et al, 2017;Jardim et al, 2020b;Jardim et al, 2021b;Silva et al, 2020c). A palma forrageira possibilita a produção animal nos períodos mais críticos do ano, surgindo como fonte alternativa de alimento, pois oferece boa disponibilidade no período seco, bom coeficiente de digestibilidade da matéria seca e alta produtividade.…”
Section: Origem E Distribuição Da Palma Forrageiraunclassified